Transforming troubled lives strategies and interventions with children with social, emotional and behavioural difficulties - Visser, John, 1946-; Daniels, Harry; Cole, Ted (International perspectives in inclusive education,, 2012)
As inclusive practice becomes more embedded in the policy and practice of schools around the globe, there remains groups of children and young people for whom education is a problem because of the behaviours, poor emotional development and lack of social skills. These pupils often display disaffection towards education and are to be found on the margins of mainstream schools too often they dropout of schooling altogether. Drawing on papers and discussions at the third International Conference of SEBDA in 2010 at Keble College ,Oxford, UK, the papers in this volume both describe and critically examine strategies and interventions in meeting the educational and well being needs of these children and young people. The contributions provide insights into the ways in which these pupils can remain engaged, or even be persuaded to re-engage, in education provided in both mainstream and specialist schools.